STRUKTUR MODAL, UKURAN PERUSAHAAN DAN NILAI PERUSAHAAN - Wulandari -; Yudhistira Ardana (Jurnal Bisnis Darmajaya, 2018)
From the expected income in the future. Good financial management can maximize company value. This study aims to determine the effect of capital structure and firm size on firm value. The sample in this study were manufacturing companies listed on the Indonesia Stock Exchange in the period 20014-2016. The method of determining the sample used was purposive sampling. By using several predetermined criteria, this study uses 39 manufacturing companies. The data analysis technique used in this study is multiple linear regression analysis. The results in this study indicate that: 1) capital structure does not affect the value of the company, 2) the size of the company has a negative and significant effect on firm value.Keywords - Capital Structure, Company Size, Company Value.